Hemorrhoidal disease: what role can rectal artery embolization play? - Panneau, Julien; Mege, Diane; Di Bisceglie, Mathieu; Duclos, Julie; Khati, Idir; Vidal, Vincent; Gallo, Gaetano; Tradi, Farouk (Frontiers in Surgery, 2025)
IntroductionHemorrhoidal artery embolization, also known as Emborrhoid, has emerged in recent years as a minimally invasive treatment option for patients with recurrent and unresponsive to medical therapies hemorrhoidal bleeding symptoms. We present here an overview of the profile of rectal artery embolization based on the most relevant and recent literature.MethodsA comprehensive review of literature on Hemorrhoidal artery embolization, was conducted on PubMed–Medline. The most relevant literature was summarized narratively.ResultsCurrent literature confirms the feasibility, efficacy and safety of rectal artery embolization for bleeding hemorrhoids. To date, the results of nearly 250 patients who have undergone hemorrhoid embolization have been published in several studies. All these authors have reported high immediate technical success, with also high clinical success, ranging from 63% to 94%, without major complications. Because of its beneficial safety profile, rectal artery embolization represents an attractive option for selected patients. In case of recurrence of bleeding it is possible to consider repeating the embolization procedure. Treatment failure may be due to the presence of anatomical variants such as dominant middle rectal arteries, which can be investigated and treated in the second session if necessary.ConclusionRectal artery embolization represents a valuable addition to the therapeutic armamentarium of bleeding hemorrhoidal disease, if patients are selected appropriately.